Repeated Acquisition and Discrimination Reversal in the Squirrel Monkey (Saimiri sciureus) - Kangas, Brian D. (2013)
Repeated acquisition and discrimination reversal tasks are often used to examine behavioral relations of, respectively, learning and cognitive flexibility. Surprisingly, despite their frequent use in cognitive neuroscience and behavioral pharmacology, variables that control performance under these two tasks have not been widely studied. The present studies were conducted to directly investigate the controlling variables in nonhuman primates. Squirrel monkeys were trained with a touchscreen variant of the repeated acquisition task in which a novel pair of S(+)/S(−) stimuli was presented daily. Subjects learned to discriminate the two stimuli (acquisition) and, subsequently, with the contingencies switched (reversal). Results indicate that rates of both acquisition and reversal learning increased across successive sessions, but that rate of reversal learning remained slower than acquisition learning, i.e., more trials were needed for mastery. Subsequent experiments showed this difference between the rate of learning novel discriminations and reversal was reliable for at least 5 days between acquisition and reversal and notwithstanding the interpolation of additional discriminations. Experimental analysis of the S(+)/S(−) elements of the tasks revealed that the difference in the rate of learning could not be attributed to a relatively aversive quality of the S(−) or to a relatively appetitive quality of the S(+) but, rather, to contextual control by the S(+)/S(−) stimulus complex. Thus, if either element (S(+) or S(−)) of the stimulus complex was replaced by a novel stimulus, the rate of acquisition approximated that expected with a novel stimulus pair. These results improve our understanding of fundamental features of discrimination acquisition and reversal.